The mechanism of layer formation and the function of additives used in fully formulated engine crankcase oils - Kaleli, H; Berthier, Y (ELSEVIER SCIENCE BV, 2002)
Lubricant additives are chemicals which, when present in small amounts, improve the physical, chemical or tribological properties of the lubricant. They form a tribochemical (antiwear) film on the rubbing surfaces which protect the engine from excessive wear. In this study fully formulated crankcase oil (SAE 20W50) is used to investigate the role of additives and determine the mechanical conditions of the formation of protective additive layers between sliding surfaces. As many and various scientifical work exist on additive tribo-chemistry, we are mostly oriented on tribo-mechanics. In what mechanical conditions such as coefficient of friction, velocity, temperature, surface roughness, load and lubrication condition (hydrodynamic or boundary) additives play their role appropriately? Tests were performed on a reciprocating pin-on-plate machine using steel and steel sliding partners under boundary lubrication conditions. Various tests were carried out at different loads, velocities and temperatures then the conclusions were demonstrated using analytical methods such as light microscopy, electron microscopy and X-Ray diffraction. Although various results were obtained, low coefficient of friction, slightly worn surface and drop of oil mostly in boundary conditions play an important role to have partial additive layers (as a small islands) covering the wear scar. Additive layers have mostly been detected in the darkest grooves (such as additive's islands) of the slightly worn surfaces in the case of using Scanning Electron microscopy. X-Ray maps show that darker points contain more additives elements such as Ca, Zn, P, S and Cl than lighter points.
Keywords: tribo-mechanics; additive protective layer; coefficient of friction; wear; Engineering